SOCIAL COMMERCE AND STUDENT DECISION-MAKING: A NARRATIVE LITERATURE REVIEW IN EDUCATIONAL CONTEXTS - Sahetapy, Kenneth; Ambalao, Shapely Smart (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of social commerce has significantly transformed how individuals, particularly students, make decisions in digital environments. This study aims to synthesize existing literature on social commerce and student decision-making within educational contexts. A narrative literature review approach was employed by analyzing 20 peer-reviewed articles published between 2010 and 2024, sourced from academic databases such as Scopus, Google Scholar, and ScienceDirect. The selected studies were analyzed thematically to identify key determinants influencing decision-making processes. The findings reveal that trust is the most dominant factor shaping student decision-making, followed by social influence, electronic word-of-mouth (e-WOM), and platform characteristics. These factors interact within algorithm-driven digital environments, where user-generated content and social interactions significantly affect perception, evaluation, and behavioral intention. The study further highlights that students operate in hybrid digital ecosystems where social interaction, learning processes, and consumption behaviors intersect. As a result, decision-making is not solely an individual cognitive process but a socially mediated and technologically influenced phenomenon. This review contributes to the literature by integrating fragmented findings into a comprehensive framework that explains how social, technological, and behavioral factors collectively shape student decision-making in social commerce contexts. The study also emphasizes the importance of digital literacy and critical thinking skills in enabling students to navigate complex online environments effectively. Future research is recommended to explore algorithmic influence and cross-cultural variations in student behavior within social commerce ecosystems